PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS PADA MATERI KEANEKARAGAMAN HAYATI DI MAN 1 MEDAN - Ashar Hasairin; Dewi Apriyanti (Jurnal Pelita Pendidikan, 2018)
This study aims to determine the improvement of student learning result and activities by using the cooperative learning model of Talking Chips type on the subject matter of Biodiversity in class X MIA1 MAN 1 Medan T.P. 2018/2019. The research method is classroom action research and the subject of this research are students of class X MIA1 as many as 35 people. The instrument that used in the study are test of student learning result namely pretest and postest as many as 30 questions and observation sheets of student activities. The results showed that based on the learning result of the first cycle, the average score of pretest was 40.6 increased to 68.6 in the postest. At the second cycle, there was an increase from 62.8 in the pretest to 74.5 in the postest. In this study, the data of individual and classical learning completeness criteria are obtained as follows: as many as 30 out of 35 students or 85.72% who scored above 70 or equal to 70, and 5 other students or 14.28% got a score below 70. Based on observations of student activities, the percentage of students who were active in the first cycle was 48.2% with total of students 17 out of 35 students, and students who were active in the second cycle was 80% with total of students 28 from 35 students